Fractional Order Sliding Mode Control to Mitigate Power Quality Issues using Dynamic Voltage Restorer in Distribution Network - Yaqub, Muhammad Haroon; Hanif, Aamir; Anwar, Naveed; Ullah, Mian Farhan; Shah, Muhammad Shahzaib; Hussein, Aziza I. (IAES Indonesian Section, 2025)
Power quality (PQ) issues lead industrial customers to suffer significant financial losses. These PQ issues are garnering more attention from electricity suppliers and consumers in the modern day. This study addresses prevalent PQ issues, namely voltage sag and swell, stemming from a decrease in RMS voltage within electrical networks, particularly impacting sensitive loads. The solution proposed involves employing a series connected custom power device (CPD) named as dynamic voltage restorer (DVR) with an integrated DC battery for energy storage, to consistently maintain the requisite voltage magnitude. To effectively combat voltage sag and swell, the study introduces a novel control strategy known as fractional order sliding mode control (FOSMC). Noteworthy features of the FOSMC methodology include its capacity to autonomously and dynamically address sag and swell issues. The Simscape toolbox of MATLAB®/Simulink® is used to perform simulations to showcase the efficacy of the FOSMC technique. The results demonstrate that this strategy ensures total harmonic distortion remains below 5% and achieves sag/swell mitigation in less than 2 milliseconds, aligning with SEMI-F-47 and IEEE voltage standard 1159-2019. In summary, the study introduces and validates a robust control strategy implemented in a DVR system to autonomously alleviate voltage sag and swell issues, with simulation results supporting its effectiveness in upholding PQ standards. The FOSMC scheme with DVR is also compared with FOSMC scheme with DSTATCOM as well as with super twisting sliding mode control (STSMC) algorithm and classical sliding mode controller (SMC) to show the effectiveness of the proposed scheme. The FOSMC technique with DVR is more effective in restoring voltage sag/swell and PQ issues.